PENGEMBANGAN APLIKASI AKUNTANSI SEDERHANA BERBASIS WEB DENGAN BAHASA PEMOGRAMAN PHP, DATABASE MYSQL - Gabiel Gesa Widi Purnomo; Totok Dewayanto (Diponegoro Journal of Accounting, 2025)
This study aims to develop a simple accounting application that can be used by companies, organizations to manage their financial data or as educational material for the general public about accounting practices. Currently, the entry of transaction data is usually done manually by financial staff. Financial transactions can only be done on local computers, so if the financial staff or the person concerned is out of the office, they cannot make transactions. This is an obstacle for managers, because this data is very important to know the financial condition of the company. Seeing the problems that occur, it is necessary to create an accounting application that can help the work of the finance department and managers in viewing financial information. The system development method used in this study is incremental. In this application there are accounting logics that are used to calculate transactions and balances from the accounts used. The result of this application is a financial report addressed to the manager. Ultimately, this application can help the work of the finance department in entering transactions and managers in viewing financial reports